PÉREZ NAVARRO, P. (2023). Orden y peligro. Por una deslocalización queer. Barcelona: Bellaterra - Bello Reguera, Gabriel (Daimon Revista Internacional de Filosofia, 2025)
Reseña de PÉREZ NAVARRO, P. (2023). Orden y peligro. Por una deslocalización queer. Barcelona: Bellaterra.